Long-term effects of high-intensity interval training, moderate-to-vigorous intensity continuous training and Nordic walking on physical and mental health in patients with coronary artery disease. (11th May 2022) - Terada, T; Cotie, L; Tulloch, H; Mistura, M; Vidal-Almela, S; O'neill, C; Reid, R; Pipe, A; Reed, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Canadian Institutes of Health Research (CIHR) Postdoctoral Fellowship Background/Introduction: Twelve weeks of high-intensity interval training (HIIT), moderate-to-vigorous intensity continuous training (MICT) and Nordic walking (NW) have been shown to improve functional capacity, quality of life (QoL) and depression in patients with coronary artery disease (CAD). However, their long-term effects are unknown. Purpose: The primary purpose was to compare the long-term effects and sustainability of 12 weeks of HIIT, MICT and NW on functional capacity. The secondary purpose was to assess the long-term effects and sustainability of 12 weeks of HIIT, MICT and NW on QoL and depression severity. Methods: Patients with CAD were randomized to a 12-week HIIT, MICT or NW program. Functional capacity, QoL and depression severity were measured at baseline, at the end of 12 weeks of intervention, and following 14 weeks of observation phase (week 26). Functional capacity was measured with a 6-minute walk test (6MWT); QoL was assessed by the HeartQoL and Short-Form-36; and depression severity by the Beck Depression Inventory-II (BDI-II). The long-term effects (changes between baseline and week 26) and sustainability (changes between week 12 and week 26) were assessed by linear mixed models for repeated measures. Results: Of 130 participants randomized, 86 (HIIT: n=29, MICT: n=27, NW: n=30) completed week 26 assessments. There were significant improvements in 6MWT distance (F=149.657, p<0.001), QoL and depression severity (both p<0.05) from baseline to week 26; the increase in 6MWT distance was greater for NW when compared to MICT (F=7.021, p=0.010) and HIIT (F=5.279, p=0.025, Figure). Between week 12 and week 26, 6MWT distance (F=10.863, p=0.001) and physical QoL (physical component summary [PCS]; F=4.084, p=0.047) increased significantly, whereas mental QoL significantly decreased (mental component summary [MCS]; F=4.052, p=0.047). Conclusion: HIIT, MICT and NW have positive long-term impacts on functional capacity, QoL and depression severity. However, NW was shown to confer additional benefits in increasing long-term functional capacity. The positive effects of the 12-week exercise programs were sustained at week 26 except for mental QoL.